UKRAINE AND GREAT RUSSIAN POWER: CHRISTIAN RAKOVSKY VERSUS JOSEPH STALIN, 1922-23 - Markwick, Roger D. (Дриновський збірник, 2024)
The article is devoted to Ch. Rakovsky's views on the development and construction of Ukraine in 1922-1923. In this context, after the Bolsheviks began to gain power in Ukraine in 1919, he did not rely much on national self-determination. But after the introduction of the New Economic Policy (NEP) in 1921, Rakovsky adjusted his views, supported the expansion of Ukraine's autonomy and advocated the need to give more independence to some state bodies. This led to conflicts with another famous Soviet figure, Joseph Stalin. The article reveals the main points of tension between Rakovsky and Stalin, different approaches to issues of centralization of power and "nationalization", and touches on "great-Russian chauvinism".